Uwarunkowania eksploatacji kruszywa naturalnego z rzeki Bóbr w obszarze chronionego krajobrazu "25 - Dolina Bobru" = Conditions of exploitation natural aggregates in Bóbr river at the protected landscape area "25 ? Bóbr Valley" - Asani, Anna; Gawron, Marta; Kołodziejczyk, Urszula (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Article provides a procedure about applying for a permit for extraction of aggregates in the landscape conservation area "25 - Bóbr Valley", located in the region of Nowgoród Bobrzański. The abolition of the current ban on the use of aggregate in the landscape protected area, is a necessary condition to obtain a permit for extraction of natural aggregate from the Bóbr river bed, on a stretch from km 48 +640 to km 49 +050.
Keywords: eksploatacja kruszywa naturalnego; Bóbr (rzeka); obszary chronionego krajobrazu; Bóbr River; exploitation of natural aggregate; protected landscape areas